Republic of Estonia : Technical Assistance Report-Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2021)
The government of Estonia places a high importance on openness and transparency, both for their citizens and for regional and international partners. This is evidenced from various earlier reports on transparency and the implementation of many subsequent improvements in fiscal transparency practices. The objective of the assessment was to identify areas of fiscal risk vulnerabilities and reform priorities to ensure further improvements in transparent practices.